Monitoring and Behavior of Biomotor Skills in Futsal Athletes During a Season - Stochi de Oliveira, Ricardo; Borin, João Paulo (Frontiers in Psychology, 2021)
Futsal is a sport that presents alternation of high and low intensity moments, which lacks investigations regarding the effects of the organization of the training load on biomotor skills. In this sense, this study aims to verify the monitoring of the training load throughout the season and the behavior of biomotor skills in futsal athletes. Twelve futsal athletes (24.5±4.9 years, 1.79±0.6 m, 72.4±9.4 kg and 9.4±4.3% fat) from the adult category who competed in the first division of the Paulista championship participated in the study. Throughout the season the internal training load (ITL) was calculated, through the relationship between volume (minutes) and the rate of perceived exertion (RPE), monotony and training strain. The training periods were divided into: preparatory, competitive and competitive II, for a total of four moments of evaluation: M1: at the beginning of the preparatory period; M2: 5th week, at the end of the preparatory period; M3: 13th week, in the middle of the competitive period and M4: at the start of the competitive period II. The tests used were: i) Power of lower limbs: counter movement jump (CMJ); ii) Displacement speed, over the 10-meter distance (V10m) and iii) Aerobic power, by the Carminatti test (T-CAR). The variables analyzed were compared at the different moments of evaluation using the two-way ANOVA completed by the Bonferroni test. For monotony, training strain and ILT the ANOVA ONE-WAY test was used between the evaluation periods completed by the Bonferroni test. The significance value adopted was p<0.05. A significant improvement (p<0.05) was observed in the power of lower limbs from M1 (37.5±5.5 cm) to M3 (40.8±5.7 cm), from M2 (38.9±5.5 cm) to M3 (40.8±5.7 cm) and from M1 (37.5±5.5 cm) to M4 (40.2±5.4 cm). Aerobic power showed a significant increase (p <0.05) from M1 (12.1±0.7 km/h) to M3 (12.7±7 km/h) and from M1 (12.1±0.7 km/h) to M4 (12.73±1.04 km/h). The internal training load showed a difference between competitive I and II in relation to the preparatory period (p<0.05). In conclusion, the proposed training organization was sufficient to improve the power of the lower limbs and the aerobic power.